Sebuah Interpretative Phenomenological Analysis tentang Makna Kelahiran Anak bagi Ibu Pascapengalaman Keguguran - PRAVITASARI, ARVINDA; Desiningrum, Dinie Ratri (Empati, 2017)
Miscarriage is a very impactful phenomenon to a mother. One of it is the post-miscarriage depression to excessive fear and anxiety towards the next pregnancy. The focus of this research is to explore more about the mother’s experience in a process to understand the meaning of birth and parenting of a child, related to the effect of the miscarriage that she experienced beforehand. This research aims to grasp how miscarriage can give significant impact to the mother after the child born. Purposive sampling is used to find four participants that are mothers who have experienced miscarriage. The interviews were done semi-structurally which then transcripted and analyzed using interpretative phenomenological analysis (IPA). There are three main themes that are found: (1) pregnancy and miscarriage experience (2) childbirth for mother (3) social support. This research gives chance to participants to talk about their experience regarding the process of understanding the child and the parenting process that they applied to their children. Findings in this research can be inputs to understand more about the psychological impact of miscarriage to a mother and how it affects the process of parenting and understanding the children.